2017
DOI: 10.1124/jpet.116.239160
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Characterization of Valbenazine (NBI-98854) and Its Metabolites

Abstract: The vesicular monoamine transporter 2 (VMAT2) is an integral presynaptic protein that regulates the packaging and subsequent release of dopamine and other monoamines from neuronal vesicles into the synapse. Valbenazine (NBI-98854), a novel compound that selectively inhibits VMAT2, is approved for the treatment of tardive dyskinesia. Valbenazine is converted to two significant circulating metabolites in vivo, namely, (+)--dihydrotetrabenazine (R,R,R-HTBZ) and a mono-oxy metabolite, NBI-136110. Radioligand-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 237 publications
(94 citation statements)
references
References 31 publications
1
93
0
Order By: Relevance
“…These are similar to the values observed with the non‐deuterated metabolites of tetrabenazine, with Ki values of 3.1 and 20 nM, respectively. Deuteration does not appear to cause a significant difference in the off‐target receptor binding profile compared with tetrabenazine; however, the affinity for other receptors is generally low, although one of the isomers of non‐deuterated β‐HTBZ has a Ki of 53 nM to the dopamine D2 receptor, as reported in the literature, and for which the clinical significance is unclear given the lack of a strong signal for parkinsonism in clinical trials of deutetrabenazine for TD…”
Section: Data Synthesismentioning
confidence: 83%
See 1 more Smart Citation
“…These are similar to the values observed with the non‐deuterated metabolites of tetrabenazine, with Ki values of 3.1 and 20 nM, respectively. Deuteration does not appear to cause a significant difference in the off‐target receptor binding profile compared with tetrabenazine; however, the affinity for other receptors is generally low, although one of the isomers of non‐deuterated β‐HTBZ has a Ki of 53 nM to the dopamine D2 receptor, as reported in the literature, and for which the clinical significance is unclear given the lack of a strong signal for parkinsonism in clinical trials of deutetrabenazine for TD…”
Section: Data Synthesismentioning
confidence: 83%
“…Deuteration does not appear to cause a significant difference in the off-target receptor binding profile compared with tetrabenazine; 34 however, the affinity for other receptors is generally low, although one of the isomers of non-deuterated β-HTBZ has a Ki of 53 nM to the dopamine D2 receptor, as reported in the literature, 45 and for which the clinical significance is unclear given the lack of a strong signal for parkinsonism in clinical trials of deutetrabenazine for TD. 1 were comparable or higher than tetrabenazine 25 mg but were associated with longer half-lives and lower maximum concentrations that occurred later.…”
Section: Inhibition Of Vmat2 Binding Differs Among Deutetrabenazine'smentioning
confidence: 85%
“…Valbenazine has two major metabolites: [+]-α-HTBZ (or R,R,R-HTBZ), which is formed by hydrolysis and is a common metabolite with tetrabenazine, and NBI-136110, which is formed by mono-oxidation. Studies have shown that these two metabolites have no affinity for other unintended targets [22]. This pharmacologic profile contributes to a lower potential for side effects and reduced concerns over pharmacokinetic drug interactions or the need to screen for CYP2D6 polymorphisms.…”
mentioning
confidence: 99%
“…Valbenazine is a novel and highly selective VMAT2 inhibitor that is rapidly absorbed but more slowly metabolized, with a half-life of approximately 20 h that supports oncedaily dosing [22,26]. Valbenazine has two major metabolites: [+]-α-HTBZ (or R,R,R-HTBZ), which is formed by hydrolysis and is a common metabolite with tetrabenazine, and NBI-136110, which is formed by mono-oxidation.…”
mentioning
confidence: 99%
See 1 more Smart Citation